Isolation and characterization of an analgesic constituent from the leaves of Albizia lebbekoides (DC) Benth Family Leguminosae. - Woldemariam, Yohannes Negussie
An analgesic constituent from the leaves of Albizia lebbekoides (DC) Benth was isolated from the hexane layer by sequential liquid chromatographic methods. Its isolation and purification was bioassay directed. Review of related literature and spectral analyses showed that the elucidated compound is 3β, 16α-Dihydroxyolean-6(7), 12(13)-dien-28-oic acid a new pentacyclic triterpenoid with an oleanene skeletal structure. At a dosage of 62.50 mg/kg mouse, it exhibited 75.4% analgesic activity using the acetic acid-induced writhing test. Statistical analysis showed that significance is less than 0.000 with F-value 10.288, thus the null hypothesis, µ1 = µ2, is rejected and therefore, there is enough evidence to say that 3β, 16α-Dihydroxyolean-6(7), 12(13)-dien-28-oic acid has significant analgesic activity at 95% level of significance
Computer print out.
Keywords: Medicinal plants -- Therapeutic us